Thermoluminescence measurements of entrance surface skin dose in exams of dog's chest in veterinary radiology - Veneziani, G. R. [UNESP]; Matsushima, L. C.; Fernandez, R. M. [UNESP]; Rodrigues, L. L. (Pergamon-Elsevier B.V. Ltd, 2010)
This study aims to determine the entrance surface skin doses in dogs (with suspected pulmonary metastasis) submitted to chest X-rays using the technique of thermoluminescence (TL) dosimetry. Twenty seven radiologic exams of dogs of different breed and sizes were performed. The radiation doses were assessed using thermoluminescent dosimeters of calcium sulphate doped with dysprosium (CaSO(4):Dy) produced at Instituto de Pesquisas Energeticas e Nucleares (IPEN-CNEN). The entrance surface skin dose range evaluated in this type of procedure was between 0.43 mGy to small size dogs and 4.22 mGy to big size dogs with repeated exams. The obtained results indicate that is extremely important the assessment of radiation doses involved in veterinary diagnostic radiology procedures, to evaluate the delivered doses to the animals, to be used as a parameter in the individual monitoring of pet's owners, who assist the animal positioning, and to protect occupationally exposed workers at the Veterinary Radiology Clinics. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Entrance surface skin dose; Thermoluminescence dosimetry; Veterinary radiology